Aplikasi Rencana Pemotongan Plat Menggunakan Sistem Pakar - Muhriyana, Ryan; Burhanuddin, Yanuar; Panuju, Achmad Yahya T (FT UNILA, 2013)
In each plate cutting, design is paramount in the cutting plan. Cutting plan was made to minimize costs, wages designers, reducing the lead time required to order and improve the accuracy of estimated production costs. To help address the difficulties in cutting plate, it needs to be an expert system application expertise, bringing together designers each cut plate. The system created is an expert system for plate cutting plan is done by designing a program with the cutting plate in accordance with the wishes of the user using Visual Basic programming language 6.0. Where in the making users create data base using microsoft acces then applied into Visual Basic 6.0. Although this application is simply to cut the plate arrives squares and rectangles only, but with this program engineer can determine the total and the rest of the plate to be cut before the plate was cut.Keywords: expert system, cutting plate, rest of plate cutting